ФОЛЬКЛОР ВА ОММАВИЙ АХБОРОТ ВОСИТАЛАРИНИНГ ТАРИХАН СИНКРЕТЛИГИ - Ахмедова, О.М. (SCIENCE and SOCIETY, 2022)
This study discusses the exchange of information, interaction as an important condition for the existence and development of society, the syncretism of ancient journalism - proto-journalism and folklore, folklore carriers, ancient mythology, archaic religions as primary media, common and different aspects of journalism and folklore. In journalism, scientific research related to the historical classification of mass communications into two periods has been theoretically studied.
Keywords: folklore; journalism; proto-journalism; syncretism